Association of Fusobacterium nucleatum with colorectal cancer molecular subtypes and its outcome: a systematic review - Luana Greco; Federica Rubbino; Clarissa Ferrari; Michela Cameletti; Fabio Grizzi; Fabrizio Bonelli; Alberto Malesci; Massimiliano Mazzone; Luigi Ricciardiello; Luigi Laghi (Gut Microbiome)
Colorectal cancer (CRC) represents a relevant public health problem, with high incidence and mortality in Western countries. CRC can occur as sporadic (65%–75%), common familial (25%), or as a consequence of an inherited predisposition (up to 10%). While unravelling its genetic basis has been a long trip leading to relevant clinical implementation over more than 30 years, other contributing factors remain to be clarified. Among these, micro-organisms have emerged as critical players in the development and progression of the disease, as well as for CRC treatment response. Fusobacterium nucleatum (Fn) has been associated with CRC development in both pre-clinical models and clinical settings. Fusobacteria are core members of the human oral microbiome, while being less prevalent in the healthy gut, prompting questions about their localization in CRC and its precursor lesions. This review aims to critically discuss the evidence connecting Fn with CRC pathogenesis, its molecular subtypes and clinical outcomes.